2003
DOI: 10.1128/iai.71.3.1470-1480.2003
|View full text |Cite
|
Sign up to set email alerts
|

CD14- and Toll-Like Receptor-Dependent Activation of Bladder Epithelial Cells by Lipopolysaccharide and Type 1 PiliatedEscherichia coli

Abstract: The gram-negative bacterium Escherichia coli is the leading cause of urinary tract infection. The interaction between type 1 piliated E. coli and bladder epithelial cells leads to the rapid production of inflammatory mediators, such as interleukin-6 (IL-6) and IL-8. Conflicting reports have been published in the literature regarding the mechanism by which uroepithelial cells are activated by type 1 piliated E. coli. In particular, the role of lipopolysaccharide (LPS) in these responses has been an area of sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
138
2
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(150 citation statements)
references
References 51 publications
5
138
2
3
Order By: Relevance
“…During the first 24 h after a single transurethral inoculation of 1-2 ϫ 10 7 CFUs, UTI89 binds to and invades the bladder urothelium. This host-pathogen interaction activates several innate defenses (40)(41)(42). A fraction of the original inoculum is able to survive or subvert host defenses, invade superficial umbrella cells, escape into the cytoplasm, and rapidly replicate into IBCs.…”
Section: Results Fimh Gene Is Under Positive Selection In a Subset Ofmentioning
confidence: 99%
“…During the first 24 h after a single transurethral inoculation of 1-2 ϫ 10 7 CFUs, UTI89 binds to and invades the bladder urothelium. This host-pathogen interaction activates several innate defenses (40)(41)(42). A fraction of the original inoculum is able to survive or subvert host defenses, invade superficial umbrella cells, escape into the cytoplasm, and rapidly replicate into IBCs.…”
Section: Results Fimh Gene Is Under Positive Selection In a Subset Ofmentioning
confidence: 99%
“…Epithelial cells must be protected from constant TLR activation by commensals and their PAMP, in order for mucosal integrity to be maintained. The epithelial cells thus lack co-receptors like CD14 [6][7][8][9][10][11], and in addition, commensals have been suggested to actively suppress epithelia responses through NF-jB [12,13]. Yet, mucosal pathogens evoke rapid TLR4-dependent responses at mucosal sites, suggesting that alternative ligands and receptors might be involved in mucosal TLR activation.…”
Section: Introductionmentioning
confidence: 99%
“…There is good evidence from a number of epidemiological studies that P fimbriae are important in upper UTI (Johnson, 1991). While the mechanism is debatable (Hedlund et al, 1999;Schilling et al, 2003), P-fimbrial expression has been shown to induce inflammation in humans and in a mouse model. A current model provides evidence for P-fimbrial adherence provoking inflammation in a cluster of differentiation number 14 (CD-14)-independent manner, probably by association with toll-like receptor number 4 (TLR-4) (Frendeus et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…There is good evidence from a number of epidemiological studies that P fimbriae are important in upper UTI (Johnson, 1991). While the mechanism is debatable (Hedlund et al, 1999;Schilling et al, 2003), P-fimbrial expression has been shown to induce inflammation in humans and in a mouse model. A current model provides evidence for P-fimbrial Abbreviations: GFP, green fluorescent protein; HA, haemagglutination; Lrp, leucine-responsive regulatory protein; MRHA, mannose-resistant HA; MSHA, mannose-sensitive HA; Pap, pyelonephritis-associated pili; Prf, Pap-related fimbriae; RBC, red blood cell; Sfa, S-fimbrial adhesin; UPEC, uropathogenic E. coli; UTI, urinary tract infection.…”
mentioning
confidence: 99%